Proposed codification of ethicacy in the publication process - Carland, Jo Ann (Journal of business ethics, 1992)
The pressure for publication is ever present in academe. Rules for submission are elucidated by conferences, proceedings and journals for the benefit of authors; however, the rules for reviewers and editors are not so well established or consistent. This treatise examines examples of abuse of the editorial process and points to a need for formal recognition of rules for review. The manuscript culminates with proposed Codes of Ethics for researchers, referees and editors and suggestions for improvement of the peer review process.